2022
DOI: 10.1080/16549716.2021.2019391
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a three-pillar training intervention to improve maternal and neonatal healthcare in the Democratic Republic Of Congo: a process evaluation study in an urban health zone

Abstract: Background Numerous quality-improvement projects including healthcare professional training are conducted globally every year, but there is a gap between the knowledge obtained in the training and its implementation in practice and policy. A quality-improvement programme was conducted in eastern Democratic Republic of Congo (DRC) to reduce maternal and neonatal mortality and morbidity. Objective This study explores the implementation process, mechanisms of impact, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Bolan et al utilized the Theoretical Domains Framework at the construct level in interview question development and at the domain level in their analysis, mapping interview responses to eight of the 14 domains [ 83 ]. Berg et al report using an “exploratory design guided by the principles of an evaluation framework” developed by the Medical Research Council to analyze the implementation process, mechanisms of impact, and outcomes of a three-pillar training intervention to improve maternal and neonatal healthcare in the conflict-affected South Kivu province of the DRC [ 67 , 88 ]. Select components of this evaluation framework were used to guide deductive analysis of focus group discussions and in-depth interviews [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolan et al utilized the Theoretical Domains Framework at the construct level in interview question development and at the domain level in their analysis, mapping interview responses to eight of the 14 domains [ 83 ]. Berg et al report using an “exploratory design guided by the principles of an evaluation framework” developed by the Medical Research Council to analyze the implementation process, mechanisms of impact, and outcomes of a three-pillar training intervention to improve maternal and neonatal healthcare in the conflict-affected South Kivu province of the DRC [ 67 , 88 ]. Select components of this evaluation framework were used to guide deductive analysis of focus group discussions and in-depth interviews [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Berg et al report using an “exploratory design guided by the principles of an evaluation framework” developed by the Medical Research Council to analyze the implementation process, mechanisms of impact, and outcomes of a three-pillar training intervention to improve maternal and neonatal healthcare in the conflict-affected South Kivu province of the DRC [ 67 , 88 ]. Select components of this evaluation framework were used to guide deductive analysis of focus group discussions and in-depth interviews [ 67 ]. In their study of health workers’ knowledge and attitudes toward newborn health interventions in South Sudan, before and after training and supply provision, Sami et al report use of the Conceptual Framework of the Role of Attitudes in Evidence-Based Practice Implementation in their analysis process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research argues that midwifery curricula according to international standards are deficient in key competencies necessary for delivering high-quality childbirth care in DRC [ 27 ]. Another study from DRC identified a shortage of simulation-based learning activities and inadequate materials at clinical sites for midwifery education programmes [ 28 ]. Notably, both midwifery educators and clinical preceptors acknowledged insufficient competencies, affecting their ability and quality of instruction [ 29 ].…”
Section: Introductionmentioning
confidence: 99%